Synthesis, Characterization and Antibacterial Activity Study of Cobalt(II), Nickel(II), Copper(II), Palladium(II), Cadmium(II) and Platinum(IV) Complexes with 4-Amino-5-(3,4,5-trimethoxyphenyl)-4H-1,2,4-triazole-3-thione - Waleed Abbas Jawad; Asim Alaa Abd Al-Hussein Balakit; Mahmoud Najim Abid Al-Jibouri (Indonesian Journal of Chemistry, 2021)
New transition metal complexes of cobalt(II), nickel(II), copper(II), palladium(II), cadmium(II), and platinum(IV) with bidentate ligand 4-amino-5-(3,4,5-trimethoxyphenyl)-4H-1,2,4-triazole-3-thiol were synthesized and characterized by microelemental analyses (CHNS), Fourier-transform infrared (FT-IR), UV-Visible spectra, molar conductance, magnetic susceptibility and thermal analyses (TG-DSC). The ligand was synthesized by ring closure of potassium-2-(3,4,5-trimethoxybenzoyl) hydrazine carbodithioate with an excess amount of hydrazine, and then was acidified using hydrochloric acid. The ligand was used as Lewis bases to prepare metal complexes through the reaction of ratio (1:2) metal:ligand. The ligand was characterized by 1H-NMR and 13C-NMR and the previously described methods to identify the complexes. The results obtained from spectra and elemental analyses indicated the tetrahedral geometry around Cd(II) ion, square-planar for Cu(II) and Pd(II), and octahedral geometry around Co(II), Ni(II), and Pt(IV). All the metal complexes showed significant antibacterial activity in comparison with the free ligand. The antibacterial test of the platinum(IV) complex showed higher activity than other metal complexes against bacteria Staphylococcus aureus (G-positive) and Escherichia coli (G-negative).